Human Herpesvirus Infection Biological Features, Transmission, Symptoms, Diagnosis and Treatment - Luis Thomasini, Ronaldo (IntechOpen, 2020)
The relationship between herpesviruses and humans probably dates from thousands of years ago. In the last few decades, many aspects of herpesvirus infections have been understood, such as infections with a range of manifestations (severe, mild, or subclinical). Herpesvirus can remain latent during a lifetime and sometimes their reactivation can cause different clinical features in the patient. Several conditions have been related to herpesvirus reactivation such as complications in transplant organ recipients and immune regulatory modification in the elderly. Aspects of human herpesvirus simples, varicella-zoster virus, and cytomegalovirus are presented and discussed in this book.